A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP OF UNRI IN PROVIDING WORDS TO COMPLETE THE SUMMARY OF A TEXT - Lusi Marleni (Journal of English Language and Education, 2016)
The students reading comprehension can be measured by test. One of them is by giving the text with consisting blanks, or a summary cloze test. This research is a descriptive research which describe the ability of the fourth semester students of English Study Program of FKIP of University of Riau in providing word(s) to complete a text. After analyzing the data of the students ability in providing word(s) to complete a text, the writer comes to the conclusions that the mean score of students is 58.7. It means that the level of ability of the fourth semester students of English Study Program of FKIP of University of Riau in providing words to complete a text is in mediocre level and most of them (23 out of students or 62.2%) are in good level.